The European phenomenon : European airline environmental reporting : a research report submitted in partial fulfillment of the requirements for the degree of Master of Philosophy (Management), from Massey University - Day, Benjamin R (Massey University, 1999)
It is generally accepted that the earth is facing some serious ecological issues as the world's population increases and as the environmental impacts of human endeavour take effect. Business, and the consumption that it promotes, is often blamed for the environmental dilemmas that the earth is facing (Hawken, 1994; Welford, 1995). However, as business becomes more responsible and accountable a new phenomenon has emerged in the process of environmental management and environmental accountability (Deloitte Touche Tohmatsu, 1993). A new catch phrase can now be heard echoing in the boardrooms all around the world, as companies begin a journey of environmental and social responsibility. Corporate Environmental Reporting or CER is a new tool in the arsenal for business and is often part of a broad environmental management process. Several commentators argue that environmental reporting is an extremely important tool in the journey towards business sustainability because CER is seen as a method of gaining trust and credibility. Honesty is an important part of the whole sustainability argument; environmental disclosure is a method for business to achieve this (UNEP, 1994; Sustain Ability, 1997).
Keywords: Airlines -- Environmental aspects; Europe; Corporation reports; Environmental policy